Socio-Demographic Profile, Etiology and Visual Outcome of Traumatic Cataract in North–West Rajasthan - Rashmi Joshi; Rekha Kumari Goyal; Anju Kochar (Delhi Journal of Ophthalmology)
Purpose: To study the socio-demographic profile, etiology and visual outcome of traumatic cataract in North-west Rajasthan. Material and Method: This cross-sectional study was done on 50 patients who presented in department of opthalmology from January 2016 to May 2017. Relevant clinical history, demographic data and visual acuity at time of presentation and post-operatively after two month were recorded. All data were compiled and managed on SSPS. Results: Among 50 patients, majority of patients were young adult between age 21-30 yr, male representation greater than female. Wooden stick trauma constituted the major fraction (n=22, 44%). Most of patients had penetrating injury (n=36, 72%) and poor visual acuity at presentation. Conclusion: Males face increased risk of trauma due to engagement in outdoor activities. Penetrating injuries are associated with poor visual outcome post-operatively because of association of other complication like corneal opacity, scarring and irregular astigmatism.